Winding Down, Facing Up: Insights gained on the road to retirement - Paul Pender (Qualitative Research in Medicine & Healthcare)
Before you can become a good storyteller, you first must be a good listener. Practicing clinical ophthalmology for 38 years allowed me to absorb the stories of my patients. Showing them signs of trust - a firm handshake, a smile, a facial expression of concern - let them know that I was there for them from the beginning. (...)